(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Egg production traits are quantitative trait in nature that control by regions of the genome are termed microsatellites that considered to be association with this trait. This review was aimed to provide information related to polymorphism egg production trait of local chickens and association with microsatellites markers.